Anesthetic neurotoxicity in the developing brain: an update on theinsights and implications for fetal surgery - Cinquegrana, Denise; Boppana, Sri Harsha; Berman, David; Nguyen, Truc-Anh T.; Baschat, Ahmet A.; Murphy, Jamie; Mintz, C. David (Anesthesia and pain medicine (Korean society of anesthesiologists), 2024)
This review describes an in-depth analysis of the neurotoxicity associated with the anesthetic agents used during fetal surgery, intending to highlight the importance of understanding the effects of general anesthetics on the developing brain, particularly in the context of open fetal surgery, where high doses are applied to facilitate surgical access and augment uterine relaxation. We examined evidence from preclinical studies in rodents and primates, along with studies in human subjects, with the results collectively suggesting that general anesthetics can disrupt brain development and lead to long-lasting neurological deficits. Our review underscores the clinical implications of these findings, indicating an association between extensive anesthetic exposure in early life and subsequent cognitive deficits. The current standard of anesthetic care for fetal surgical procedures was scrutinized, and recommendations have been proposed to mitigate the risk of anesthetic neurotoxicity. These recommendations emphasize the need for careful selection of anesthetic techniques to minimize fetal exposure to potentially harmful agents. In conclusion, while the benefits of fetal surgery in addressing immediate risks often outweigh the potential neurotoxic effects of anesthesia, the long-term developmental impacts nevertheless warrant consideration. Our analysis suggests that the use of general anesthetics in fetal surgery, especially at high doses, poses a significant risk of developmental neurotoxicity. As such, it is imperative to explore safer alternatives, such as employing different methods of uterine relaxation and minimizing the use of general anesthetics, to achieve the necessary surgical conditions. Further research, particularly in clinical settings, is essential to fully understand the risks and benefits of anesthetic techniques in fetal surgery.